2003
DOI: 10.1002/chem.200390143
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Photophysical, and Electrophosphorescent Properties of Platinum(II) Complexes Supported by Tetradentate N2O2 Chelates

Abstract: We present an examination of the structural and photophysical characteristics of [Pt(N(2)O(2))] complexes bearing bis(phenoxy)diimine auxiliaries (diimine=4,7-Ph(2)phen (1) and 4,4'-tBu(2)bpy (2)) that are tetradentate relatives of the quinolinolato (q) ligand. These neutral derivatives display high thermal stability (>400 degrees C in N(2)). While the crystal lattice in 1 consists of (head-to-tail)-interacting dimers, molecules of 2 are arranged into infinitely stacked planar sheets with possible pi-pi intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…Such negative solvato- www.chemeurj.org chromism is consistent with the polar character of the electron-rich phenoxide ring in the ground state. This finding may suggest an involvement of partial charge transfer from a phenoxide ring to an imine in the salen-centered transition, similar to that found in the salen-Pt derivatives [17,19] and the 8-hydroxyquinoline-related metal complexes [20,37] (vide infra).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Such negative solvato- www.chemeurj.org chromism is consistent with the polar character of the electron-rich phenoxide ring in the ground state. This finding may suggest an involvement of partial charge transfer from a phenoxide ring to an imine in the salen-centered transition, similar to that found in the salen-Pt derivatives [17,19] and the 8-hydroxyquinoline-related metal complexes [20,37] (vide infra).…”
Section: Resultsmentioning
confidence: 71%
“…Furthermore, the salen ligands have often been employed in the phosphorescent emitters based on platinum. [17][18][19][20] All these reports have prompted us to consider whether the salen-Al complexes could be utilized as versatile materials for OLEDs; our group has recently demonstrated that the pentacoordinated salen-Al complexes with an aryloxy ancillary ligand can serve not only as efficient hole-blocking materials [21] for phosphorescent OLEDs, but also as hosts in the dopant assembly OLEDs based on a heterodinuclear Al/Ir complex. [22] They found that the salen-Al complexes possess suitable HOMO and LUMO energy levels, high thermal stability, and high PL efficiency, all of which may render them promising as emitting materials in OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Several complexes with 6,6'-diphenyl-2,2'bipyridine ligand derivatives have been reported. [28,29] We therefore adapted some of the previous protocols to prepare our new ligand (7)a nd corresponding metal complexes (4 and 5). AS uzuki cross-couplingr eactionu sing 6,6'-dibromo-2,2'-bipyridine and 2,4-dimethoxyphenyl boronic acid was carried out, followed by demethylation with boron tribromide to yield compound 7.T he phenolic scaffold was metalated by using Ni 2 + or VO 2 + salts to yield the corresponding metal-bipyridine precursor complexes 8 and 9,w hichw ere then reacted with chloroethyl piperidine to yield the new complexes 4 and 5.I t should be pointed out that no vanadyl complexes with 6,6'-diphenyl-2,2'-bipyridine ligandsh ave been previously reported.…”
Section: Design and Synthesis Of Metal Complexesmentioning
confidence: 99%
“…One approach to further rigidify the platinum complex framework is to adopt tetradentate ligands composed of C, N, or O donors. The use of Schiff base or hydroxyphenyl substituted phenanthroline platinum complexes for OLED applications was reported in early 2000s . A series of O 2 N 2 type Schiff base platinum complexes was synthesized and their photophysical and OLED properties were investigated.…”
Section: Phosphorescent Transition Metal Complexesmentioning
confidence: 99%